2021
DOI: 10.3389/fmed.2021.729030
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone and Estradiol as Novel Prognostic Indicators for HBV-Related Acute-on-Chronic Liver Failure

Abstract: Background: HBV-related acute-on-chronic liver failure (HBV-ACLF) has a high short-term mortality and urgently needs an early warning system with simplicity and high accuracy. Previous studies show that sex hormones play potential roles in the progression of HBV-related liver diseases.Aims: To explore the effect of testosterone and estradiol on the occurrence and prognosis of HBV-ACLF.Methods: A prospective cohort of 300 chronic hepatitis B (CHB) patients was enrolled among which 108 were diagnosed with HBV-AC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…In PBC patients under 40, the level of estrogen (E2) was below the reference range for fertile women. As reported earlier, low levels of estradiol [ 30 ] or testosterone [ 31 , 32 ] could predict mortality in chronic liver diseases. In addition, we found that the level of DHEA in both younger and older PBC patients was still within the reference range for healthy females.…”
Section: Discussionmentioning
confidence: 90%
“…In PBC patients under 40, the level of estrogen (E2) was below the reference range for fertile women. As reported earlier, low levels of estradiol [ 30 ] or testosterone [ 31 , 32 ] could predict mortality in chronic liver diseases. In addition, we found that the level of DHEA in both younger and older PBC patients was still within the reference range for healthy females.…”
Section: Discussionmentioning
confidence: 90%
“…Several studies have shown a relationship between testosterone and liver injury ( Al-Qudimat et al, 2021 ). Even though testosterone treatment improves liver injury and metabolic syndrome, and its effect on type two diabetes mellitus is well-documented ( Sun et al, 2021 ), testosterone effects on hepatic injury are still limited. In the present study, we conducted an experimental prospective study on the effect of testosterone treatment on liver injury by assessing liver enzymes, metabolic and oxidative stress, and real-time PCR for the liver and prostate.…”
Section: Discussionmentioning
confidence: 99%
“…45,46 In cohort study noticed that hormone level significantly changes HBV-related acute-on-chronic liver failure (HBV-ACLF) and HCC patients. 47,48 Besides, hormone related therapy reduced HCC risk and improved survival outcome in HBV infection female patients. 49,50 Thus, Sex hormone and related receptors play important roles in gender disparity in HBV infection and HCC.…”
Section: Gender Disparity In the Prevalence And Development Of Hbv-re...mentioning
confidence: 99%
“…In vivo studies found that sex hormones regulated HBV replication and transcription, and estrogen supplement suppress chemical‐induced HCC cells proliferation 45,46 . In cohort study noticed that hormone level significantly changes HBV‐related acute‐on‐chronic liver failure (HBV‐ACLF) and HCC patients 47,48 . Besides, hormone related therapy reduced HCC risk and improved survival outcome in HBV infection female patients 49,50 .…”
Section: Gender Disparity In the Prevalence And Development Of Hbv‐re...mentioning
confidence: 99%